Bacterial Adaptation during Chronic Respiratory Infections - Louise Cullen; Siobhán McClean (Pathogens, 2015)
Chronic lung infections are associated with increased morbidity and mortality for individuals with underlying respiratory conditions such as cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD). The process of chronic colonisation allows pathogens to adapt over time to cope with changing selection pressures, co-infecting species and antimicrobial therapies. These adaptations can occur due to environmental pressures in the lung such as inflammatory responses, hypoxia, nutrient deficiency, osmolarity, low pH and antibiotic therapies. Phenotypic adaptations in bacterial pathogens from acute to chronic infection include, but are not limited to, antibiotic resistance, exopolysaccharide production (mucoidy), loss in motility, formation of small colony variants, increased mutation rate, quorum sensing and altered production of virulence factors associated with chronic infection. The evolution of Pseudomonas aeruginosa during chronic lung infection has been widely studied. More recently, the adaptations that other chronically colonising respiratory pathogens, including Staphylococcus aureus, Burkholderia cepacia complex and Haemophilus influenzae undergo during chronic infection have also been investigated. This review aims to examine the adaptations utilised by different bacterial pathogens to aid in their evolution from acute to chronic pathogens of the immunocompromised lung including CF and COPD.